2014
DOI: 10.1016/j.heares.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Auditory cortex activation to natural speech and simulated cochlear implant speech measured with functional near-infrared spectroscopy

Abstract: The primary goal of most cochlear implant procedures is to improve a patient’s ability to discriminate speech. To accomplish this, cochlear implants are programmed so as to maximize speech understanding. However, programming a cochlear implant can be an iterative, labor-intensive process that takes place over months. In this study, we sought to determine whether functional near-infrared spectroscopy (fNIRS), a non-invasive neuroimaging method which is safe to use repeatedly and for extended periods of time, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
174
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 178 publications
(181 citation statements)
references
References 39 publications
7
174
0
Order By: Relevance
“…The two-dimensional interpolated T-statistic map was projected to the cortical surface and the cortex surface was colored based on the projected T-statistic values. This strategy is reasonable given our previously published work demonstrating that the responses measured with fNIRS derive from this region of the brain (Sevy et al 2010; Pollonini et al 2014). However, it is important to note that this plotting scheme has no impact on the individual or group statistical analyses performed in this manuscript.…”
Section: Methodssupporting
confidence: 72%
See 4 more Smart Citations
“…The two-dimensional interpolated T-statistic map was projected to the cortical surface and the cortex surface was colored based on the projected T-statistic values. This strategy is reasonable given our previously published work demonstrating that the responses measured with fNIRS derive from this region of the brain (Sevy et al 2010; Pollonini et al 2014). However, it is important to note that this plotting scheme has no impact on the individual or group statistical analyses performed in this manuscript.…”
Section: Methodssupporting
confidence: 72%
“…Previously, our group demonstrated that fNIRS can detect speech-evoked activation of the LTL/STG, a core region of the auditory cortex in normal hearing and implanted participants. In addition, we found that adults with normal hearing exhibit greater cortical activation to speech than non-speech sounds (Sevy et al 2010; Pollonini et al 2014). Here, we expand this approach in participants with CIs to explore the use of fNIRS as an objective measure of speech perception.…”
mentioning
confidence: 79%
See 3 more Smart Citations